2010
DOI: 10.11646/zootaxa.2691.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Calyptraeotheres Campos, 1990 (Crustacea, Decapoda, Brachyura, Pinnotheridae) with the description of C. pepeluisi new species from the tropical Mexican Pacific

Abstract: A reassessment of the adult and larval morphology as well as comparison with published molecular information confirms the monophyly of the genus Calyptraeotheres Campos, 1990, and its relationship with Dissodactylus Smith, 1870, Clypeasterophilus Campos & Griffith, 1990 and Tumidotheres Campos, 1990. Calyptraeotheres pepeluisi new species, is described from Michoacán, Mexico on the basis of a female specimen. The new species is distinguished from the other nominal species of the genus by having a subarcuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Understanding the systematics of this family has been the aim of many studies, which have generally been based on comparative morphology (e.g. Griffith, ; Manning & Felder, ; Marques & Pohle, ; Ahyong & Ng, ; Campos, ; Campos & Hernández‐Ávila, ) and more recently have included molecular data (Harrison, ; Harrison & Hanley, ; Palacios‐Theil et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the systematics of this family has been the aim of many studies, which have generally been based on comparative morphology (e.g. Griffith, ; Manning & Felder, ; Marques & Pohle, ; Ahyong & Ng, ; Campos, ; Campos & Hernández‐Ávila, ) and more recently have included molecular data (Harrison, ; Harrison & Hanley, ; Palacios‐Theil et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Calyptraeotheres Campos, 1990, is an American genus belonging to Pinnotheridae, in which all members are obligatory symbionts of slipper limpets of the family Calyptraeidae (Campos, ). Within this genus, composed of five species (see Campos & Hernández‐Ávila, ), Calyptraeotheres garthi (Fenucci, ) is distributed from the San Matias Gulf in Argentina to the coast of Rio Grande do Sul in southern Brazil (Martins & D'Incao, ), where it lives in symbiotic association with almost all naturally occurring limpets of the Calyptraeidae family (Ocampo et al ., ). Calyptraeotheres politus (Smith, 1870) is found along the south‐eastern Pacific coast, living in limpets of the genera Crepipatella and Calyptraea (Campos, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phylogenetic study based on the corrected zoeal data matrix of Marques & Pohle (1995) confirmed sister-group relationships between Sakaina and Parapinnixa (cf. Campos & Hernández-Ávila, 2010). In the cladograms mentioned, the genus Asthenognathus represents a basal taxon (Pohle & Marques, 1998) or is used as the outgroup (Campos & Hernández-Ávila, 2010).…”
Section: S Yokoyai S Japonicamentioning
confidence: 99%
“…Campos & Hernández-Ávila, 2010). In the cladograms mentioned, the genus Asthenognathus represents a basal taxon (Pohle & Marques, 1998) or is used as the outgroup (Campos & Hernández-Ávila, 2010).…”
Section: S Yokoyai S Japonicamentioning
confidence: 99%